Ischaemic stroke, haemorrhage, and mortality in older patients with chronic kidney disease newly started on anticoagulation for atrial fibrillation: a population based study from UK primary care. (14th February 2018) - Kumar, Shankar; de Lusignan, Simon; McGovern, Andrew; Correa, Ana; Hriskova, Mariya; Gatenby, Piers; Jones, Simon; Goldsmith, David; Camm, A John
Abstract: Objective: To assess the association between anticoagulation, ischaemic stroke, gastrointestinal and cerebral haemorrhage, and all cause mortality in older people with atrial fibrillation and chronic kidney disease. Design: Propensity matched, population based, retrospective cohort analysis from January 2006 through December 2016. Setting: The Royal College of General Practitioners Research and Surveillance Centre database population of almost 2.73 million patients from 110 general practices across England and Wales. Participants: Patients aged 65 years and over with a new diagnosis of atrial fibrillation and estimated glomerular filtration rate (eGFR) of <50 mL/min/1.73m 2, calculated using the chronic kidney disease epidemiology collaboration creatinine equation. Patients with a previous diagnosis of atrial fibrillation or receiving anticoagulation in the preceding 120 days were excluded, as were patients requiring dialysis and recipients of renal transplants. Intervention: Receipt of an anticoagulant prescription within 60 days of atrial fibrillation diagnosis. Main outcome measures: Ischaemic stroke, cerebral or gastrointestinal haemorrhage, and all cause mortality. Results: 6977 patients with chronic kidney disease and newly diagnosed atrial fibrillation were identified, of whom 2434 were on anticoagulants within 60 days of diagnosis and 4543 were not. 2434 pairs were matched using propensity scores by exposure to anticoagulant or none and followed for a median of 506 days. The crude rates for ischaemic stroke and haemorrhage were 4.6 and 1.2 after taking anticoagulants and 1.5 and 0.4 in patients who were not taking anticoagulant per 100 person years, respectively. The hazard ratios for ischaemic stroke, haemorrhage, and all cause mortality for those on anticoagulants were 2.60 (95% confidence interval 2.00 to 3.38), 2.42 (1.44 to 4.05), and 0.82 (0.74 to 0.91) compared with those who received no anticoagulation. Conclusion: Giving anticoagulants to older people with concomitant atrial fibrillation and chronic kidney disease was associated with an increased rate of ischaemic stroke and haemorrhage but a paradoxical lowered rate of all cause mortality. Careful consideration should be given before starting anticoagulants in older people with chronic kidney disease who develop atrial fibrillation. There remains an urgent need for adequately powered randomised trials in this population to explore these findings and to provide clarity on correct clinical management.